A lei das estatais e suas repercussões nas estruturas de governança corporativa das empresas de energia elétrica - Mainieri, Fernanda Cortes Lopes (Universidade do Vale do Rio dos Sinos, 2018)
The Law 13303/2016 entered the legal world with a "mission" to discipline the status of public and mixed-capital companies. The initiative came up against a worrying scenario, with controversial economic results and scandals of corruption, making clear the fragility of state organization and management. Faced with a need to restructure the public governance model, the new requirements of this Law created a basis for a more formal, impersonal and robust decision-making process, supported by management mechanisms, transparency and adequate metrics to determine and communicate the results of its operations. And in practice, what is the real impact this Law has brought to the public companies? In the present study, the objective was to verify the influence of the changes imposed by the Law and what their impact on the corporate governance structures of the public companies is, especially the eletric company, given the characteristics of the electric industry and because the distributors have regulatory agencies with a high level of requirement for compliance with its normative rules. Interviews were conducted with three companies and the results indicate that the impact of the State Law was minimal, due to other rules imposed by bodies with CVM, B3 and ANEEL. Even so, it was unanimous both among the companies surveyed as to the bibliographic revision made, that a differentiated rule was necessary for the public companies. It is time for new forms of governance and control mechanisms (mainly in the political field) to cease to be theoretical expressions and be applied in practice. And that state-owned companies that do not adapt or change their way of acting will no longer be able to justify their existence.
Keywords: Lei das Estatais; Governança corporativa; Compliance; Energia elétrica; State Law; Corporate Governance; Compliance; Electric Power; ACCNPQ::Ciências Sociais Aplicadas::Direito